2003
DOI: 10.1007/s00203-003-0584-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and properties of novel deglycating enzymes for fructosyl peptide in fungi

Abstract: Our fungal culture collection was screened for fructosyl peptide oxidase, an enzyme that could be used for the determination of glycated hemoglobin in diabetic subjects with hyperglycemia. Fructosyl peptide oxidases were found in strains of eight genera: Achaetomiella, Achaetomium, Chaetomium, Coniochaeta, Eupenicillium, Gelasinospora, Microascus and Thielavia. By their substrate specificity toward N(alpha)-fructosyl valyl-histidine (alpha-keto-amine) and N(epsilon)-fructosyl lysine (epsilon-keto-amine), fruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Fru-hexapeptide, Fru-ValHis and valyl-histidine (ValHis) were measured by HPLC on an Amide-80 column (£ 4.6 mm  25 cm; Tosoh, Japan) with 30% KH 2 PO 4 (10 mM) in acetonitrile as a solvent at a flow rate of 1.0 ml/min with monitoring of the absorbance at 205 nm [14]. Fru-hexapeptide, Fru-ValHis and ValHis were used as controls for the HPLC analysis.…”
Section: Identification Of Proteolysis and Deglycation Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fru-hexapeptide, Fru-ValHis and valyl-histidine (ValHis) were measured by HPLC on an Amide-80 column (£ 4.6 mm  25 cm; Tosoh, Japan) with 30% KH 2 PO 4 (10 mM) in acetonitrile as a solvent at a flow rate of 1.0 ml/min with monitoring of the absorbance at 205 nm [14]. Fru-hexapeptide, Fru-ValHis and ValHis were used as controls for the HPLC analysis.…”
Section: Identification Of Proteolysis and Deglycation Productsmentioning
confidence: 99%
“…showed specificity toward N e -(1-deoxyfructosyl)-N a -Z-Lys, N -(1-deoxyfructosyl)-Val (Fru-Val) and/or fructosyl propylamine [12,9,13]. Recently, we screened a fungal culture collection for fructosyl peptide oxidase (FPOX) using N -(1-deoxyfructosyl)-Val-His (Fru-ValHis) as a substrate [14]. We found that the cell extracts of several genera of fungi showed FPOX activity and then purified and characterized two FPOXs; one from Eupenicillium terrenum ATCC18547 and one from Coniochaeta sp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we screened a fungal culture collection and isolated a novel type of FAOX from Eupenicillium terrenum ATCC18547 and from Coniochaeta sp. NISL9330 (Hirokawa et al 2003a). These deglycating enzymes showed specificity towards both fructosyl amino acids and fructosyl peptides such as N-(1-deoxyfructosyl)-Val-His (Fru-ValHis), while previously isolated FAOXs were only active against fructosyl amino acids (Hirokawa et al 2003b).…”
Section: Introductionmentioning
confidence: 96%
“…Fructosyl amine oxidases (FAOXs) are FAD-containing enzymes that catalyze the oxidative deglycosylation of fructosyl amino acids such as fructosyl valine and/or ε-fructosyl lysine, which are the degradation products of HbA1c and GA, respectively. As members of the FAOX family, fructosyl peptide oxidases (FPOXs) are also known as candidates for diagnostic enzymes 6 . A few promising FPOXs derived from Eupenicillium terrenum (EtFPOX) and Coniochaeta sp.…”
Section: Introductionmentioning
confidence: 99%